2003
DOI: 10.1023/a:1024413918346
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, social functioning, and feelings of hatred and revenge of Kosovar Albanians one year after the war in Kosovo

Abstract: A cross-sectional cluster sample survey was conducted in June 2000 in Kosovo to assess the prevalence of mental health problems associated with traumatic experiences, feelings of hatred and revenge, and the level of social functioning among Kosovar Albanians approximately 1 year after the end of the war. Findings of the second cross-sectional survey were compared with those from our 1999 mental health survey in Kosovo. Included in the survey were 1399 Kosovar Albanians aged 15 years or older living in 593 rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 18 publications
4
97
0
Order By: Relevance
“…On one hand, right-wing attitudes were associated with the sort of "dark" and vengeful inclinations found in previous studies to predict PTSD reactions (e.g., Cardozo et al, 2003). Right-wing authoritarianism, conservatism, and conservative shift were all associated with increased cynicism and a greater desire for vengeance following the 9/11 attacks.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On one hand, right-wing attitudes were associated with the sort of "dark" and vengeful inclinations found in previous studies to predict PTSD reactions (e.g., Cardozo et al, 2003). Right-wing authoritarianism, conservatism, and conservative shift were all associated with increased cynicism and a greater desire for vengeance following the 9/11 attacks.…”
Section: Discussionmentioning
confidence: 67%
“…For example, thoughts of revenge in the context of perceived injustice, such as in response to crime, are associated with increased PTSD symptoms, and this relationship becomes stronger over time (Orth, Montada, & Maercker, 2005). The magnitude of hatred and desire for revenge also predicts psychiatric symptoms among populations exposed to ethnic atrocities and ethnically motivated war (Cardozo, Kaiser, Gotway, & Agani, 2003). It is also noteworthy that thoughts of revenge are associated with PTSD even among individuals who have been exposed to environmental disasters, situations in which there may be no clearly identifiable perpetrator (Goenjian, Molina, et al, 2001).…”
mentioning
confidence: 99%
“…Furthermore, the shame and loss of self-confidence associated with such events may enhance the vulnerability to posttraumatic stress disorder (PTSD) and depression . PTSD after war experiences has also been shown to be related to feelings of hatred and revenge (Cardozo, Kaiser, Gotway, & Agani, 2003).…”
mentioning
confidence: 99%
“…It has one of the largest population of migrants (21% in 2003) of all European countries and migrants from Ex-Yugoslavia are the second largest subpopulation today. One study found prevalence rates of 25% for PTSD in Kosovarian Albanians one year after the war (Cardozo 2003). Another study in Kosovarian Albanians who returned home two years after the end of the conflict from their country of asylum (Switzerland) showed prevalence rates of 23.5% (Eytan A et al 2004).…”
Section: Ptsd: Background and Significance Of Expected Resultsmentioning
confidence: 99%